2018
DOI: 10.1016/s1872-2067(17)62919-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the microstructures and catalytic behaviors of iron–oxygen precursors during direct coal liquefaction

Abstract: A series of both unsupported and coal-supported iron-oxygen compounds with gradual changes in microstructure were synthesized by a precipitation-oxidation process at 20 to 70 °C. The relationship between the microstructures and catalytic activities of these precursors during direct coal liquefaction was studied. The results show that the microstructure could be controlled through adjusting the synthesis temperature during the precipitation-oxidation procedure, and that compounds synthesized at lower temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Currently, iron-based catalysts are widely used due to their simple production methods, low prices, and no need for recovery. FeOOH has a high specific surface area, stable physicochemical properties, and special particle structure, which can be easily transformed into iron sulfide with a small particle size, excellent catalytic activity, and good stability. , Traditional methods of FeOOH preparation mainly include room-temperature solid-phase method, aniline method, hydrothermal method, sol–gel method, chemical precipitation method, air oxidation method, and mechanical-force solid-phase method . The advantages of the mechanical-force solid-phase method for the preparation of FeOOH are mild reaction conditions, high yield, no solvent, simple process, and low-energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, iron-based catalysts are widely used due to their simple production methods, low prices, and no need for recovery. FeOOH has a high specific surface area, stable physicochemical properties, and special particle structure, which can be easily transformed into iron sulfide with a small particle size, excellent catalytic activity, and good stability. , Traditional methods of FeOOH preparation mainly include room-temperature solid-phase method, aniline method, hydrothermal method, sol–gel method, chemical precipitation method, air oxidation method, and mechanical-force solid-phase method . The advantages of the mechanical-force solid-phase method for the preparation of FeOOH are mild reaction conditions, high yield, no solvent, simple process, and low-energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xie et al studied the relationship between catalyst microstructure and catalytic behavior during the catalytic conversion of coal. in particular, the effects of different crystal shapes and morphologies on the catalytic activity [ 32 ]. Wang et al reported that lamellar MoS 2 was more easily inserted into macromolecules, thus improving the catalytic hydrogenation performance [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…As more and more people are keen on developing innovative hydrogenation catalysts, the pace of progress in this area is accelerating. Low-cost and environmentally friendly Fe-based particle or supported catalysts (Kuznetsov et al 2000;Kaneko et al 2002;Sheng et al 2017;Zhou et al 2018;Xie et al 2018;Lokhat et al 2019;) have been widely studied and applied in industrial installations. Unfortunately, the mediocre hydrogenation performance of iron catalyst results in general performance in coal-oil co-processing.…”
Section: Introductionmentioning
confidence: 99%